Mesin Panas Kuantum dengan Sistem Multipartikel dan Multi Keadaan: Heru Sukamto, Agus Purwanto, Bintoro Anang Subagyo - Heru Sukamto, Heru Sukamto; Agus Purwanto, Agus Purwanto; Bintoro Anang Subagyo, Bintoro Anang Subagyo (Jurnal Fisika dan Aplikasinya, 2025)
In this paper, we present quantum heat engine with m fermion in p state in one-dimensional potential well as working substance. The Carnot circle is considered, with two iso-energetic process and two iso-entropic process. We consider generalize transition state after iso-energetic process. Then we determine an expansion parameter that maximize power output for each configuration transition state. We also calculate a pair of expansion parameter and configuration of transition state that maximize output power.